Belarusian Tiles of the 16th‒17th Centuries in the Collection of the Russian Museum - Popova, Elena A. (Actual Problems of Theory and History of Art, 2024)
The group of medieval stove tiles was discovered during the excavations in the ancient town of Novogrudok in the 1950–60s. In 1979, 73 items were included in the collection of the State Russian Museum. The tradition of decorating stoves with ceramic tiles came to Belarusian cities and castles from Germany. The most ancient type of tiles from Novogrudok resembles a cylindrical vessel and is dated to the mid-14th century. However, most of the exhibits from the museum collection belong to the 17th century. Some of the tiles are glazed. There are two types of glaze: self-colored green and polychrome. The front sides of the tiles were decorated with a variety of ornaments, including geometrical, floral, armorial, hieratic, and animalistic. The tiles from Novogrudok show similarities with Lithuanian and Polish pieces, yet they also display distinctive features. The artists employed a combination of modern trends and traditional schemes (such as plain geometrical patterns) in their work.